1974
DOI: 10.1136/jcp.27.9.760
|View full text |Cite
|
Sign up to set email alerts
|

Tests of disinfection by heat in a bedpan washing machine

Abstract: SYNOPSIS Tests of effectiveness of disinfection of metal and polypropylene bedpans were made in a washer fitted with a steam generator. Broth cultures of Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, or Streptococcus faecalis (approximately 4 x 108 organisms) were sealed in lengths of capillary tubing and attached to the surface of the pans. In other tests, pans were contaminated with an artificial soil containing Str. faecalis (0I organisms/ml). In both series of tests, counts of surviving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…293 Early studies showed that failure to attain 80 C was associated with persistence of E. coli and P. aeruginosa. 294 Transmission of pathogens via contaminated endoscopes is usually due to failure to comply with appropriate reprocessing practice guidelines. 295 Although some cases of transmission have been known, relatively few have been reported in peer-reviewed journals.…”
Section: Recommendationmentioning
confidence: 99%
“…293 Early studies showed that failure to attain 80 C was associated with persistence of E. coli and P. aeruginosa. 294 Transmission of pathogens via contaminated endoscopes is usually due to failure to comply with appropriate reprocessing practice guidelines. 295 Although some cases of transmission have been known, relatively few have been reported in peer-reviewed journals.…”
Section: Recommendationmentioning
confidence: 99%
“…As indicated by Ayliffe, 7 the method that requires direct contamination of tubing evaluates the effect of both heat and washing. However, the method that utilizes capillary test tubes enables one to quantify a reduction in the number of microorganisms due to the effect of heat only, because the wall of a capillary tube may simulate protection of microorganisms by organic matter.…”
Section: Discussionmentioning
confidence: 99%
“…In certain busy wards such as in medical and geriatric units, a high degree of disinfection may not be required; use of bedpan washers in these wards may be acceptable. But in high risk units the highest standard of disinfection is essential (Ayliffe et al 1974). Although the industrially coated bedpans show no advantage in disinfection over the standard bedpans their use in medical and geriatric units might be recommended because of their superior cleanability especially when cleaning may be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be room for improvement in the performance of bedpan washing machines and in the design of bedpans themselves; these points were discussed at a recent seminar held at Guy's Hospital (see editorial under 'Tomorrow's Bedpans' in B.M.J. 1974;Ayliffe, Collins & Deverill, 1974;Mostafa & Chackett, 1976a). Among other suggestions was one made by Miss A. Viant of Bristol Royal Infirmary that the spraying of bedpans with an aerosol PTFE appears to be a simple way to improve cleaning.…”
Section: Introductionmentioning
confidence: 99%